2015
DOI: 10.3390/sports3040335
|View full text |Cite
|
Sign up to set email alerts
|

Using Rowers’ Perceptions of On-Water Stroke Success to Evaluate Sculling Catch Efficiency Variables via a Boat Instrumentation System

Abstract: Abstract:Aim: An effective catch in sculling is a critical determinant of boat velocity. This study used rowers' performance-based judgments to compare three measures of catch slip efficiency. Two questions were addressed: (1) would rower-judged Yes strokes be faster than No strokes? and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…A recent study carried out on the sport field selected rowing as a setting to describe how athletes experienced their activity and the accuracy of their awareness ( Millar et al, 2015 ). While the study investigated coordination phenomena only at an intrapersonal scale, it gave insights into the role of the online lived experience of actors in regulating their action and perception dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study carried out on the sport field selected rowing as a setting to describe how athletes experienced their activity and the accuracy of their awareness ( Millar et al, 2015 ). While the study investigated coordination phenomena only at an intrapersonal scale, it gave insights into the role of the online lived experience of actors in regulating their action and perception dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Guide questions for the semi-structured interviews were developed based on similar research. 4,16 Questions incorporated the common components of the cut–roundhouse kicking combination relative to the skill level of athletes, as well as differences in skill levels (Appendix A).…”
Section: Methodsmentioning
confidence: 99%
“…This is exemplified in coach comments referring to the 'look and feel' of performance. 16 Gaps in thinking between coaches and sport scientists are captured by the work of Waters et al 17 as well as Williams and Kendall. 18 Waters et al found that biomechanists used mechanistic terminology to describe the phases of sprinting, while coaches focused more on easily observable concepts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be extended by research demonstrating expert rowers to accurately perceive and monitor their own catch efficiency, which was objectively reflected by changes in boat speed ( Millar et al, 2017 ). While to the authors’ knowledge, there has been no investigation to date into football players’ abilities to accurately self-monitor performances (under varying noise conditions), previous research commonly emphasizes “high-level performers as expert systems adept at detecting and evaluating change focussed on performance” ( Millar et al, 2015 , p. 3). Yet a special importance of these ecological factors and emotions so far has neither taken place in research, nor in the common training regimen of athletes.…”
Section: Key Concepts In Ecological Dynamics To Highlight the Importa...mentioning
confidence: 99%